João Paulo II e o diálogo inter-religioso - Silva, Claudi Gonçalves da (2012)
The dissertation has as objective to analyze the position of the Pope Juan Pablo II in relation to the interreligious dialogue, searching to understand its paradoxes, ambiguities and contributions, as well as the controversies excited for its position in the scope of the Roman Curia. To understand the relation of the Catholic Church with the not Christian ones it is mades a theological historical analysis in which it is possible to perceive that Jesus as founding of the Christianity signals the importance of the shelter and the dialogue with the people of diverse beliefs. However, throughout the centuries, the attitude of the Catholic Church, front to the other religious traditions, were marked by exclusivists positions, intolerance and combat in this trajectory Vatican Ecumenical Concíllio II (1962-1965), indicates a new attitude in relation to the interreligious dialogue. Through its trips, gestures and speeches, Juan Pablo II opens possibilities of improving the dialogue between the religions, in view of the complexity of the challenges in the humanity